Convincing the crowd: Entrepreneurial storytelling in crowdfunding campaigns. (May 2017) - Manning, Stephan; Bejarano, Thomas A
This study examines the structure of entrepreneurial stories in pursuit of mobilizing resources from crowds. Based on a comparative analysis of Kickstarter crowdfunding campaigns, we examine in particular how, across different project types, project histories and potential futures are framed and interlinked in narratives to appeal to funders. We find that projects are narrated in different styles—as "ongoing journeys" or "results-in-progress"—to convey project value. The former style narrates projects as longer-term endeavors powered by creative initial ideas and a bold vision, inviting audiences to "join the journey"; the latter narrates projects more narrowly as a progression of accomplishments, engaging the audience instrumentally to support next steps. We find that styles are used and combined in different ways, reflecting the tangibility of project outcomes, the sophistication of technology, and the social orientation of projects. Also, successful differ from unsuccessful campaigns in using narratives more coherently. Findings inform research on narrative processes in entrepreneurship and innovation, and research on the mobilization of crowds.